The Effect of Anemia in Pregnancy on Postpartum Hemorrhage - Ariyanti, Ririn; Febrianti, Selvia; Qasim, Muhammad; Jalilah, Nurul Hidayatun (JURNAL INFO KESEHATAN, 2022)
Eighty percent of maternal deaths are caused by complications during pregnancy and childbirth. Furthermore, twenty-five percent of maternal deaths is affected by postpartum hemorrhage which is estimated 100,000 deaths annually. Indonesia places at the second ranks of the highest maternal deaths country after Laos. The cause of death in Indonesia is 28% by hemorrhage.  The hemorrhage in maternity is due to anemia in pregnancy. It occurs because when the mother gives birth, there will be adequate uterine contractions so that the hemorrhage is inevitable. The objective of the study is to identify the effect of anemia in pregnancy on the incidence of postpartum hemorrhage. The type of research employed is an analytic survey with a retrospective design. The research location was at Juata Tarakan Health Center. The population in this study were all pregnant women who visited the obstetrics and gynecology polyclinic in 2020 which was obtained from secondary data, the patient's medical record book at the Juata Public Health Center with a sample of 271 on June 23 to August 31, 2021. Sampling employed a non-probability sampling technique, total sampling, and the data analysis was administered univariately, and bivariate with chi-square test. The incidence of postpartum hemorrhage in women giving birth in the working area of the Juata Tarakan Health Center is 12.9%. Anemia in pregnancy possesses a significant effect on the risk of postpartum hemorrhage with p value (OR=11,253, 95%CI 5,120-24,732). Meanwhile, parity, age, type of delivery did not possess significant effect on postpartum hemorrhage. Mothers with anemia in pregnancy own a higher risk of postpartum hemorrhage which was 11.253 times greater than mothers who were not anemic in pregnancy. Therefore, it is necessary to perform proper handling of anemia in pregnant women to prevent postpartum hemorrhage.